FACTORS AFFECTING CAPITAL EXPENDITURES AND COMMUNITY WELFARE IN KALIMANTAN - Helma Malini (Universitas Ahmad Dahlan, 2021)
From centralized to decentralized systems provides new hope for most provinces in Indonesia. With government decentralization, it means that management authority will be distributed from the center to the regions. This study aims to examine and prove whether Locally-Generated Revenue (Pendapatan Asli Daerah–PAD), Special Allocation Fund (Dana Alokasi Khusus-DAK), General Allocation Fund (Dana Alokasi Umum-DAU), Profit-Sharing Fund (Distribusi Bagi Hasil–DBH) affect capital expenditure and community welfare in Kalimantan. The population in this study are districts and cities in Kalimantan, consisting of 47 districts and 9 cities. The method used to determine the sample is purposive sampling, which selects samples with certain criteria. From a population of 56, this study examines a sample of 49 observations (42 districts and 7 cities). The results show that PAD, DAK, DAU, and DBH positively impact capital expenditure in Kalimantan. However, capital expenditure has no effect on community welfare in Kalimantan.